Pengaruh Lama Mekar Bunga Refugia Terhadap Keragaman Populasi Musuh Alami Dan Hama Pada Tanaman Padi (Oryza sativa) - Dewi Anita (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2022)
Refugia is a collection of several flowering plants breeding grounds for natural enemies. This flowering plant can attract insects because it has a variety of colors, shapes, scents, nectar, pollen, and bloom periods. This study was conducted to determine the effect of flower blooming time on the diversity of natural enemies and pests on rice plants. This study used a Randomized Block Design with five treatments and five replications. Observational data were analyzed using analysis of variance (ANOVA) with the Duncan Multiple Range (DMRT) 5% test. The variables observed were the number of arthropod pests, and natural enemies visited. The test results showed that the highest pest arthropods were found in the control treatment (P0) by 74%, and the lowest was in the Zinnia Elegans treatment (P2). The highest percentage of predators was 63% in the treatment of Zinnia Elegans (P2), while the lowest rate was in the control treatment (P0) at 24%. The highest percentage of parasitoids in the treatment Zinnia Elegans, Turnera subulata, and Mirabilis jalapa were the same at 9%, and the lowest was in the control treatment (P0) at 2%.